Hubungan Antara Derajat Sesak Napas Dengan Nilai Arus Puncak Ekspirasi Pada Pasien Asma Terkontrol Sebagian - Putri, Pritania Prameswara; Reviono; Murti, Bhisma (Jurnal Kedokteran Indonesia, 2012)
Background: Asthma is one of the most common chronic diseases and a serious global health problem. Exercise-induced asthma (EIA) is typically characterized by history of shortness of breath with exercise. However, the symptoms are not usually specific to asthma. Therefore there is a need to develop another testsuch as lung function measurement of peak expiratory flow (PEF) by using a spirometer. This study aimed to determine the correlation between perception of dyspnea and peak expiratory flow in partially controlled asthma patient. Methods:This study was a descriptive analytical research using cross sectional approach. It was conducted in April â May 2012 at Pulmonology Clinic, Dr. Moewardi General Hospital Surakarta. A sample of 35 patients was selected by purposive and random sampling with some inclusion and exclusion criteria. The sample was excluded if the result of Asthma Control Test was not below 15-19. The study subjects filled in (1) curriculum vitae form, (2) asthma control test, (3) Borg scale to find out the perception of dyspnea score. The subjects were asked to (1) Measure the peak expiratory flow by using a spirometer, (2) Exercise for 5-10 minutes. The data were analyzed using Spearman correlation on SPSS 17. Results:The study showed strong negative and statistically significant correlation of r=-0.60 (p<0.001) between perception of dyspnea and peak expiratory flow in partially controlled asthma patients. Conclusion: There is a negative correlation between perception of dyspnea and peak expiratory flow in partially controlled asthma patients. Keywords:Perception of dyspnea, peak expiratory flow (PEF), partially controlled asthma